2012
DOI: 10.3109/02713683.2012.713152
|View full text |Cite
|
Sign up to set email alerts
|

A Possible Role of Acrolein in Diabetic Retinopathy: Involvement of a VEGF/TGFβ Signaling Pathway of the Retinal Pigment Epithelium in Hyperglycemia

Abstract: Purpose Acrolein has been implicated in retinal pigment epithelium (RPE) cell death, and has been associated with diabetic retinopathy. Our purpose was to investigate the potential effect of high glucose in influencing acrolein-mediated RPE cytokine production and cell death. We investigated the influence of the acrolein effect on ARPE-19 cells in high glucose conditions and quantified the release of transforming growth factor β (TGFβ1 and 2) and vascular endothelial growth factor (VEGF). We assessed the abili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 67 publications
0
37
0
Order By: Relevance
“…The studies of Grigsby et al 20 also confirmed that VEGF secretion from ARPE-19 cells was associated with DR. Consistent with this, our results determined that NF-κB activity was strengthened in the retinas of type 2 diabetic rats and in ARPE-19 cells with high glucose stimulation.…”
Section: Discussionmentioning
confidence: 77%
“…The studies of Grigsby et al 20 also confirmed that VEGF secretion from ARPE-19 cells was associated with DR. Consistent with this, our results determined that NF-κB activity was strengthened in the retinas of type 2 diabetic rats and in ARPE-19 cells with high glucose stimulation.…”
Section: Discussionmentioning
confidence: 77%
“…Among the various oxidative modifications of proteins, carbonylation is a critical and irreparable modification that has been shown to be elevated during aging, diabetes and in neurodegeneration [12], [13], [14], [15], [16], [17], [18]. Diabetic subjects are known to have elevated glucose-, and lipoxidation-derived carbonyl stress [18], [19], [20], [21], [22], [23], however, it remains unknown if carbonylation of sciatic nerve/myelin proteins are elevated in peripheral neuropathies. Therefore, we asked (i) does oxidative stress have an effect on carbonylation and misfolding of sciatic nerve proteins in peripheral neuropathy, and (ii) is the carbonylation of sciatic nerve/myelin proteins associated with loss in nerve conduction and myelin in peripheral neuropathy?…”
Section: Introductionmentioning
confidence: 99%
“…Incubation of ARPE-19 cells in high glucose (HG) increases the expression of VEGF [27,28]. Several enzymes including NADPH oxidase are known to generate low levels of ROS [6,29].…”
Section: Resultsmentioning
confidence: 99%